Genetics and clinical correlation of Dravet syndrome and its mimics – experience of a tertiary center in Taiwan - Yi-Hsuan Liu; Yi-Ting Cheng; Meng-Han Tsai; I-Jun Chou; Po-Cheng Hung; Meng-Ying Hsieh; Yi-Shan Wang; Yun-Ju Chen; Cheng-Yen Kuo; Jainn-Jim Lin; Huei-Shyong Wang; Kuang-Lin Lin (Pediatrics and Neonatology)
Background: Dravet syndrome is a severe developmental and epileptic encephalopathy characterized by the onset of prolonged febrile and afebrile seizures in infancy and SCN1A gene mutations. In some cases, non-SCN1A gene mutations can present with a phenotype very similar to that of Dravet syndrome. The aim of this study was to compare phenotypes of patients with SCN1A and non-SCN1A gene mutation-related Dravet syndrome. Methods: Thirty-six patients with Dravet syndrome-like phenotypes were followed from July 2017 to December 2019. We retrospectively analyzed their clinical profiles and genetic surveys. Results: Of the 36 enrolled patients, 15 (41.7%) had SCN1A mutations, one (2.8%) had an SCN8A mutation, one (2.8%) had an STX1B mutation, and five females (13.9%) had PCDH 19 mutations. The median age at first seizure onset was 7 months in those with SCN1A mutations, 1.3 years in those with PCDH19 mutations, and 10 months for the remaining patients. The majority of the patients with SCN1A mutations had status epilepticus (80% vs. 20%) and fever-sensitive seizures (76% vs. 31%) compared to those with PCDH19 mutations. The patients with SCN1A-related seizures had a higher rate of focal seizures as first seizure type than those without SCN1A mutations. Three of five (60%) patients with PCDH19 mutations had brain magnetic resonance imaging abnormalities. The three most commonly used antiseizure medications were sodium valproate, levetiracetam, and clobazam. Seven of the 15 patients with SCN1A mutations used stiripentol. The median time from seizure onset to genetic diagnosis was 6.6 years (range 4 months–22.3 years). Conclusion: The patients with SCN1A mutations in this study had high rates of fever-sensitive seizures, status epilepticus, seizure onset with focal seizure type, and relatively young age at seizure onset. The patients with PCDH19 mutations had a relatively high rate of abnormal brain magnetic resonance imaging findings.